Utilization of Phule Jal Mobile App Among the University and KVK Scientists of Maharashtra State - Chavan, PM; Karangami, RS; Kharde, PB; Dhenge, SA; Kokate, K D (Indian Journal of Extension Education, 2021)
In India number of smart phone users has surpassed 204 million in recent past. Most popular mobile properties are accessed via mobile apps. This study was conducted on Irrigation Mobile App developed by Mahatma Phule Krishi Vidyapeeth, Rahuri. The study was conducted during 2016-17 on Utilization of Irrigation MobileÂ Apps by University and KVK Scientists. The investigation was carried in 10 districts with variety of geographical characteristics of Maharashtra state having the jurisdiction of Mahatma Phule Agricultural University. From selected districts 12 KVKs, 4 RECs and 5 DECs were considered for this study. 70 trained University and KVK scientists were purposively selected as respondents for the present investigation. The findings of the investigation revealed that majority of (72.86%) of the university and KVK scientists belonged to medium utilization category, followed by low (14.29%) and high (12.85%) utilization categories, respectively. Evapotranspiration (ETr) calculation feature had very frequently used by the 24.28 per cent respondentsÂ when analysed feature wise extent of utilization of Phule Jal app Frequently used features of Phule Jal mobile app were Online mode (62.86%), less frequently used feature was â€œOffline modeâ€ feature by 57.14% whereas 67.15% of the respondents were Not at all using the Evapotranspiration calculation feature.